2006
DOI: 10.1111/j.1365-2494.2006.00534.x
|View full text |Cite
|
Sign up to set email alerts
|

Dairy cow performance and labour inputs associated with two silage feeding systems

Abstract: Two experiments were conducted to examine the effect of two winter feeding systems on the performance of dairy cows in early lactation. Experiments 1 (144 d duration) and 2 (146 d duration) involved sixty-four (primiparous) and eighty-six (primiparous and multiparous) Holstein Friesian dairy cows respectively. Rations offered comprised grass silage, maize silage [0AE26-0AE29 of forage dry matter (DM)] and concentrates (10-12 kg d )1 ). With the complete diet (treatment CD), the forage and concentrate component… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0
7

Year Published

2009
2009
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 16 publications
1
19
0
7
Order By: Relevance
“…The complete diets and the forage components of the rations with the easy feed systems were offered ad libitum. Full details of each of these two feeding systems (easy feed and complete diet) have been described by Ferris et al (2006). In year 1, 32 and 48 cows were offered food via the easy feed system and complete diet system respectively (16 of the cows offered the complete diet were used in serial nutrient utilisation studies as described Ferris, Patterson, McCoy and Kilpatrick elsewhere), while in year 2, 40 cows were offered food via each of the two feeding systems.…”
Section: Treatmentsmentioning
confidence: 99%
“…The complete diets and the forage components of the rations with the easy feed systems were offered ad libitum. Full details of each of these two feeding systems (easy feed and complete diet) have been described by Ferris et al (2006). In year 1, 32 and 48 cows were offered food via the easy feed system and complete diet system respectively (16 of the cows offered the complete diet were used in serial nutrient utilisation studies as described Ferris, Patterson, McCoy and Kilpatrick elsewhere), while in year 2, 40 cows were offered food via each of the two feeding systems.…”
Section: Treatmentsmentioning
confidence: 99%
“…Maseda et al (2004) reported that this simplification plays an important role in meeting the life-quality demands made by farmers and their families. These simplifications trigger changes in work patterns by cutting the number of on-farm work tasks and the daily number of hours at work (Ferris et al, 2006).…”
Section: Resultsmentioning
confidence: 99%
“…The volume of work has increased and the number of workers has decreased in the agricultural production systems, especially in familiar agriculture (Ferris et al, 2006;Madelrieux & Dedieu, 2008;Hostiou & Dedieu, 2009). These changes were not different in dairy production.…”
Section: Introductionmentioning
confidence: 99%
“…As the agricultural working population and the number of farms have continued to fall, increasing work productivity has remained the key to farm competitiveness (Ferris et al, 2006;Aubron et al, 2009). In France, work perceptions are evolving too: farmers are increasingly focused on being free, having holidays or freeing up time to spend on private activities and the family (Dufour and Dedieu, 2010).…”
Section: Introductionmentioning
confidence: 99%